2022
DOI: 10.3390/antiox11071352
|View full text |Cite
|
Sign up to set email alerts
|

Physapruin A Induces Reactive Oxygen Species to Trigger Cytoprotective Autophagy of Breast Cancer Cells

Abstract: Physalis peruviana-derived physapruin A (PHA) is a potent compound that selectively generates reactive oxygen species (ROS) and induces cancer cell death. Autophagy, a cellular self-clearance pathway, can be induced by ROS and plays a dual role in cancer cell death. However, the role of autophagy in PHA-treated cancer cells is not understood. Our study initially showed that autophagy inhibitors such as bafilomycin A1 enhanced the cytotoxic effects of PHA in breast cancer cell lines, including MCF7 and MDA-MB-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The Hela cells were seeded on coated coverslips (0.5% gelatin and 0.05% chromium potassium sulfate) and transfected with siRNA for 48 h. The cells were then transfected with PK‐hLC3 expression vector encoding pHluorin‐mKate2‐tagged human MAP1LC3 (Tanida et al, 2014) for 24 h. The green and far‐red fluorescent proteins were imaged under an Olympus FluoView FV1000 confocal laser scanning microscope with excitation 488 (green)/588 nm (far‐red) and emission 520 (green)/633 nm (far‐red). For autophagy staining assay, oral cancer cells were stained with wither autophagosome dye (DAPGreen, 0.1 μM) or autolysosome dye (DALGreen, 0.5 μM) (Dojindo) for 30 min (Yu et al, 2022). The green fluorescence was imaged under an Olympus FluoView FV1000 confocal laser scanning microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hela cells were seeded on coated coverslips (0.5% gelatin and 0.05% chromium potassium sulfate) and transfected with siRNA for 48 h. The cells were then transfected with PK‐hLC3 expression vector encoding pHluorin‐mKate2‐tagged human MAP1LC3 (Tanida et al, 2014) for 24 h. The green and far‐red fluorescent proteins were imaged under an Olympus FluoView FV1000 confocal laser scanning microscope with excitation 488 (green)/588 nm (far‐red) and emission 520 (green)/633 nm (far‐red). For autophagy staining assay, oral cancer cells were stained with wither autophagosome dye (DAPGreen, 0.1 μM) or autolysosome dye (DALGreen, 0.5 μM) (Dojindo) for 30 min (Yu et al, 2022). The green fluorescence was imaged under an Olympus FluoView FV1000 confocal laser scanning microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The green and far-red fluorescent proteins were imaged under an Olympus FluoView FV1000 confocal laser scanning microscope with excitation 488 (green)/588 nm (far-red) and emission 520 (green)/633 nm (far-red). For autophagy staining assay, oral cancer cells were stained with wither autophagosome dye (DAPGreen, 0.1 μM) or autolysosome dye (DALGreen, 0.5 μM) (Dojindo) for 30 min (Yu et al, 2022). The green fluorescence was imaged under an Olympus FluoView FV1000 confocal laser scanning microscope.…”
Section: Confocal Microscopymentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress occurs due to the accumulation of unfolded proteins in the ER that can be caused by various physiological and pathological conditions, including oxidative stress and inflammation 11,12 . In a study, it was shown that Physapruin A, which has an antiproliferative effect, exhibited ER stress‐inducing function to promote the proliferation and apoptosis of breast cancer cells containing oxidative stress 13 …”
Section: Introductionmentioning
confidence: 99%
“…Increasing the ROS level above the redox balance in cancer cells efectively kills the cells while the ROS level below that alleviates aggressiveness by deceleration of proliferation, metastasis, and cell death induction [4]. Reduction of intracellular ROS by antioxidants on ROS-dependent cancer cells enhanced the potential of success in the treatment of metastatic solid tumors demonstrated in either in vitro or in vivo models with promising results [5,6]. In addition, numerous plantderived phytochemicals, including polyphenols and favonoids, exhibit the potential for antiproliferation and antimetastasis against cancer cells without causing cytotoxicity [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of intracellular ROS by antioxidants on ROS-dependent cancer cells enhanced the potential of success in the treatment of metastatic solid tumors demonstrated in either in vitro or in vivo models with promising results [5,6]. In addition, numerous plantderived phytochemicals, including polyphenols and favonoids, exhibit the potential for antiproliferation and antimetastasis against cancer cells without causing cytotoxicity [5][6][7].…”
Section: Introductionmentioning
confidence: 99%